Answer
y = (-1/3)x - 3
Explanation
To get the equation of a line we need; gradient of that line and and a point that lies on that line.
Firstly, we find the midpoint to get the point that lies on the required equaion.
midpoint = ((4+2)/2 , (1+ -5)/2)
= (6/2, -4/2)
= (3, -2)
Secondly, we find the gradient of the line.
gradient = Δy/Δx
= (1- -5)/(4-2)
= 6/2
= 3
The products of gradients of perpendicular line is -1.
∴ m₁ ₓ m₂ = -1
3 ₓ m₂ =-1
m₂ = -1/3
Now that we have the gradient and the point, we can find the equation a follows:
-1/3 = (y - -2)/(x-3)
-1(x-3) = 3(y+2)
-x + 3 = 3y +6
3y = -x - 3
y = (-1/3)x - 3